MODELING TELECOMMUNICATION OUTAGES DUE TO POWER LOSS - Snow, Andrew P; Weckman, Gary; Chayanam, Kavitha (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This work involves analyzing reported US telecommunications outages due to power loss over an eight year period (1996- 2003). Data from the reports includes the dateltime of each outage, allowing time series reliability analysis. The arrival process is modeled by two non-homogenous Poisson processes (NHPP): the popular power law process and a piecewise linear process. The study concludes that the number of telecommunication power outages after September II, 2001 (9-11) decreased. In this case, the frequency of outages changed abruptly, strongly inferring a change or breakpoint in fundamental process. The major fmding is that there is strong evidence of reliability growth. However, the growth could not be attributed to a monotonic "learning curve" improvement process. Rather, modeling provides strong evidence that 9-11 was episodic enough of an event to act as the catalyst for improvement